Down-regulation of Neuregulin2 (NRG2) following spinal cord injury in C57BL/6 mice: Its implications in therapeutic potential - Kai-Ye Hua; Yan-Jun Liu; Qi Ke; Quan Song; Shuai Zhang; Wei-Jiang Zhao (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): This study aims to elucidate the alterations in Neuregulin 2 (NRG2) and its receptor ErbB4 following spinal cord injury (SCI), as well as to investigate the neuroprotective mechanisms of NRG2 in neurons. Materials and Methods: Dataset GSE93561 was analyzed to verify the changes of NRG2-ErbB4 signaling pathway in mice following SCI. The levels of Iba-1 and NRG2 were analyzed by immunohistochemistry, and NRG2 and pErbB4 protein levels were detected by western blot. HT22 cells were scratched and treated with NRG2 dosed from 0–5 nM. Cell mobility was measured at the time point of 0, 24, and 48 hr after scratch. Additionally, western blot was used to detect the protein levels of pErbB4 and pAkt1 at 48 hr. Results: By analyzing dataset GSE93561, NRG1, NRG2, and NRG3 were found to be decreased to different degrees post-SCI in mice. The results of immunohistochemistry showed that the level of Iba-1 in the injured core area was significantly increased 8 weeks post-SCI. Western blot analysis showed that the protein levels of NRG2 and pErbB4 were decreased significantly post-SCI. NRG2 promoted HT22 cell migration and dose-dependently increased pErbB4 and pAkt1 protein levels at doses ranging from 0-5 nM. Conclusion: The NRG2-ErbB4 signaling pathway was inhibited after SCI in mice. NRG2 promotes the healing of HT22 cells after scratch injury, and the mechanism of NRG2 in the treatment of SCI may be ascribed to the activation of PI3K-Akt signaling pathways downstream to NRG2.